Performance of trawls to capture shrimps and fish in the “double rig” system carried out in the north coast of Brazil (Research, Society and Development, 2020)
The Trawling fisheries on the North coast are characterized by providing a large amount of fish. Due to the fact that these fisheries capture a large biomass of shrimp and fish, there was a need to assess and compare the proportion of capture of these resources using “double rig” double-trawl nets, one of which has been modified. The data were collected during the project technological innovation for selective trawls to catch fish by the shrimp fleet. In the verification of the resources, it was decided to evaluate the biomass captured in the catch of pescada gó Macrodon ancylodon and for the shrimp: the pink shrimp Farfantepenaeus subtilis and the seven beards Xiphopenaeus kroyeri. The evaluation of the proportion of catch between fish in relation to fish and shrimp were tested for both nets; the significance of the capture of the nets was also tested, in relation to the time series of the capture, through the T test of student; the CPUE (Capture / hours of trawl / day) for each trawler net was estimated, analyzing their linear correlations; normality of distribution, tested by the Shapiro-Wilk test and subsequently the analysis of variance ANOVA to check for differences significant. The modified trawler net for catching fish, obtained fish biomass higher than the shrimp net, however it captured a lower biomass of shrimp, with a higher proportion of fish, thus fulfilling its premise. Significant differences were found in the time series for capturing the nets (T: 0.017; p